Emotions and organizational governance - Härtel, Charmine E. J., 1959-; Ashkanasy, Neal M., 1945-; Zerbe, W. J. (Research on emotion in organizations, 2016)
This volume of 'Research on Emotions in Organizations' demonstrates the ubiquitousness of emotions and effects of emotions in organizational setting - starting from what goes on in the boardroom, extending right down to the way employees at the coalface interact with their customers every day.